Entrepreneurial potentials of tourism villages in Bantul Regency, Yogyakarta - Wicaksono, Ajie; Ihalauw, John JOI; Priyanto, Sony Heru (Priviet Social Sciences Journal, 2026)
Tourism villages in Yogyakarta, Indonesia, promote economic diversification, cultural preservation, and community empowerment. However, research lacks connection between heritage and innovative business strategies, affecting livelihoods. This research aims to explore the connection between cultural heritage and innovative business strategies in tourism villages in Yogyakarta, Indonesia, focusing on sustainable livelihoods and entrepreneurial ecosystems. The study employed VOSviewer analysis and a systematic literature review to explore entrepreneurial potential in tourism villages in Bantul Regency, utilizing Scopus and Google Scholar databases by using Publish or Perish application. 41 research articles were derived after conducting PRISMA analysis with some inclusion and exclusion criteria. The results show that the network visualization shows a central hub of medium to large-sized nodes, including "village," "tourism," and "Bantul Regency." Five clusters are identified, with gaps in cross-cluster integration, government-economic nexus, and capacity building metrics. The study emphasizes the need for quantitative metrics on capacity-building effects and interdisciplinary integration between cultural studies, business innovation research, and public policy analysis. It also calls for methodological advancement in measurement instruments and evaluation frameworks for rural tourism entrepreneurship.